Eucalyptus predisposition to Neofusicoccum kwambonambiense under water stress - Berenguer, Helder Duarte Paixão (2018)
In Portugal, Eucalyptus, particularly Eucalyptus globulus, occupies more than 800 000 ha and, due to being a major source of biomass for fiberboard, industrial charcoal, fuel wood and paper pulp, has become a key genus, with a considerable economic importance. However, E. globulus productivity faces new pressures, with climate change-driven drought as one of the most hostile ones. Drought can lead to growth impairment and yield reduction: directly; or indirectly, through the increase of plant susceptibility to pathogens by a predisposition mechanism. Neofusicoccum kwambonambiense is an endophytic opportunist phytopathogen known to severely affect E. globulus, whose incidence has already been reported in Portugal. Taking all in consideration, it is of major importance to assess the predisposition effect that drought may have on the N. kwambonambiense - E. globulus interaction. For such purpose, four treatment groups were established: E. globulus were firstly subjected to a 66-days acclimation period in which plants were periodically watered (80% of field capacity). After that, two groups were exposed to a progressive water supply restriction. The other two remained well-watered. Once water-stressed plants achieved 18% of field capacity (23 days), a well-watered and a water-stress group were inoculated with N. kwambonambiense. All treatments were kept in these conditions throughout a 65 days’ period, at which moment a set of morphological, physiological and biochemical parameters was obtained. Well-watered plants, despite being infected with N. kwambonambiense, presented an overall photosynthetic increase, which enabled plant defense through the production of sugars, proline and salicylic acid. Oxidative damages (partially observed through malondialdehyde content), were avoided in part due to proline and soluble sugars. Water stress lead to a direct growth impairment confirmed through an indole-acetic-acid content decrease. A water-potential reduction occurred, which, together with abscisic acid, lead to stomatal closure and overall photosynthetic efficiency decline. Oxidative damages weren’t properly managed and further affected E. globulus. Furthermore, N. kwambonambiense was found to promote a jasmonic acid content increase, typical of necrotrophic pathogens, which may suggest a lifestyle change from hemibiotrophic to necrotrophic as plant cells progressively degenerate. Ultimately, water-stressed E. globulus presented larger external lesion extensions and steam cankers and a superior internal fungi progression. Our results conclusively demonstrate that water stress created a better substrate for fungi development and decreased the plant’s ability to respond. Such resulted in higher susceptibility and disease severity confirming predisposition.